T2 Single nucleotide polymorphisms in the ficolin-2 gene predispose to Pseudomonas aeruginosa infection and disease severity in non-cystic fibrosis bronchiectasis. (2nd December 2011) - Chalmers, J D; Kilpatrick, D C; McHugh, B J; Smith, M P; Govan, J R W; Doherty, C; Matsushita, M; Hart, S P; Sethi, T; Hill, A T
Abstract : Introduction: Bronchiectasis is associated with a destructive cycle of bacterial infection, airway inflammation and airway structural damage. Ficolins are a family of recently described serum pattern recognition molecules capable of binding to micro-organisms and activating complement through MBL associated serine protease-2 (MASP-2). Their role in chronic lung disease has not previously been investigated. Methods: Serum levels of Ficolin-2 and MASP-2 were determined in 470 patients with idiopathic non-cystic fibrosis bronchiectasis and 400 matched control subjects by ELISA. Single nucleotide polymorphisms were determined using TaqMan PCR based genotyping. Bacterial binding was determined using ELISA and flow cytometry. Neutrophils from healthy donors were isolated by percoll gradient centrifugation and used in phagocytosis assays with FITC-labelled Pseudomonas aeruginosa strain PA01. Results: Genotyping success was >95% and all SNP's were in Hardy–Weinburg equilibrium (p>0.05). Bronchiectasis was associated with a homozygous mutation in the promoter of ficolin-2 (rs3124952) (28.5% vs 19.5%, p=0.002) and a homozygous mutation in exon-8 of the ficolin-2 gene causing impaired binding (rs17549193) (12% vs 8.4%, p=0.04). Low serum levels (<1.6 μg/ml, 2 SD. below the mean for controls) were strongly associated with the promoter polymorphisms (p<0.0001) and with bronchiectasis (18.7% vs 7.8%, p<0.0001). In-vitro, ficolin-2 bound to over 60 strains of P aeruginosa, including clinical isolates and mucoid strains, activating the lectin pathway of complement and promoting C3 and C4 deposition. Ficolin-2 also bound to Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus . Opsonisation with ficolin-2 promoted phagocytosis of P aeruginosa (PA01) by human neutrophils in a MASP-2 but not c1q dependent manner (p<0.0001) (Abstract T2 figure 1 ). On multivariable analysis chronic bacterial colonisation (OR=3.5; p<0.0001) and particularly P aeruginosa colonisation (OR=2.8, p=0.0001) were independently associated with ficolin-2 insufficiency. These patients also had more frequent outpatient exacerbations (mean 3.2/yr vs 2.4/yr, p=0.01) and unscheduled hospital admissions for exacerbations (OR=2.3; p<0.0001). Conclusion: Single nucleotide polymorphisms in the ficolin-2 gene affecting serum levels and carbohydrate binding are associated with non-CF bronchiectasis and increase susceptibility to colonisation with P aeruginosa.